Harmonisation of Sharia and international humanitarian law rules for the protection of Palestinian journalists in armed conflicts - Alhamadin, Yousef Y.K. (2023)
Harmonisation is more of a process. The primary purpose of harmonisation is to develop harmony between Shariah and International humanitarian law. It is not a process of ultimately harmonising these two legal systems but simply reconciling certain fair differences in a few specific areas of Shariah and international humanitarian law. Harmonization is necessary between Sharia and International humanitarian law, especially when there is a deficit in international humanitarian law regarding the protection of civilians since Islamic law covers aspects of security. This paper will discuss the Harmonisation of Sharia and International Humanitarian Law rules for the protection of journalists in armed conflicts; where International humanitarian law considers journalists civilians and sets legal rules to protect them, Islamic law is also keen to protect civilians from any dangers that may affect their lives during armed conflicts, as the Holy Qur’an, the Sunnah of the Prophet, and the sayings of jurists confirm this. The study mainly uses a descriptive-analytical approach that monitors and analyses all data and information related to Israeli violations against Palestinian journalists and media professionals and delves deeper into international law provisions and Shariah which protect journalists. As for the temporal borders, it is the period in which the 2014 war broke out, and for the spatial boundaries, it is the Gaza Strip. The expected findings show that the current international laws related to the protection of Palestinian journalists are not sufficient to eliminate violations against Palestinian journalists. Therefore, International law and Islamic law must be harmonised to provide better protection. The benefit of this paper lies in proposing some recommendations to develop the current laws to ensure better protection of the rights of Palestinian journalists and media workers, and to find effective mechanisms to punish criminals who commit crimes against journalists.